The impact of nutritional interventions on peripheral microvasculature & aspects of macrovascular blood flow in response to feeding in old age - Din, Ushnah Shujah Ud (2023)
With an ever-growing population, the number of ageing people is increasing rapidly worldwide. According to an estimate by WHO, by 2030, one in six people in the world will be aged 60 years old or over and the share of population they account for will rise from 1 billion to 1.4 billion. This steep rise will directly impact the societies or communities we are living in, and we will observe increased incidences of co-morbidities and ill health resulting in increased requirement of hospitalisation and social care needs for the older adults. This will directly increase the pressures on our healthcare services both in terms of funding and workforce requirements.